Using metacognitive cues to infer others’ thinking - Mata, André; Almeida, Tiago de (Judgment and decision making, 2014)
Three studies tested whether people use cues about the way other people think—for example, whether others respond fast vs. slow—to infer what responses other people might give to reasoning problems. People who solve reasoning problems using deliberative thinking have better insight than intuitive problem-solvers into the responses that other people might give to the same problems. Presumably because deliberative responders think of intuitive responses before they think of deliberative responses, they are aware that others might respond intuitively, particularly in circumstances that hinder deliberative thinking (e.g., fast responding). Intuitive responders, on the other hand, are less aware of alternative responses to theirs, so they infer that other people respond as they do, regardless of the way others respond. (PsycINFO Database Record (c) 2019 APA, all rights reserved)